Odpowiedzi

Najlepsza Odpowiedź!
2010-04-14T20:18:25+02:00
8. a)
4x - 3 = 3x + 5
4x - 3x = 5 + 3
x = 8

b)
5x + 2 = 7 - 3x
5x + 3x = 7 - 2
8x = 5
x = 0.625

c)
3 (x - 1) = 0
3x - 3 = 0
3x = 3
x = 1

d)
-6(x + 1) = 24
-6x - 6 = 24
-6x = 24 + 6
-6x = 30
x = -5

e)
-7(x - 2) = 3x - 1
-7x + 14 = 3x - 1
-7x - 3x = -1 - 14
-10x = -15
x = 1.5

f)
4(x - 1) = 6 (1 + x)
4x - 4 = 6 + 6x
4x - 6x = 6 + 4
-2x = 10
x = -5


9. a)
0.2x + 0.3 = -0.5
2x + 3 = -5
2x = -5 -3
x = -4

b)
0.4 + 0.25x = -2
0.25x = -2 - 0.4
0.25x = -2.4
x = -9.6

c)
2.1 - 0.3x = 0.4x
2.1 = 0.4x + 0.3x
2.1 = 0.7x
x = 3

d)
-1.5x - 3 = 0.2x + 6
-1.5x - 0.2x = 6 + 3
-1.7x = 9
x ≈ -5.3
2010-04-14T20:24:49+02:00
Zad.8
a) 4x - 3 = 3x + 5
x = 8
b) 5x + 2 = 7 - 3x
8x = 5
x= 5/8
c) 3(x-1) = 0
3x - 3 = 0
x = 1
d) -6 (x+1) = 24
-6x - 6 = 24
- 6x = 30
x = -5
e) -7 (z-2) = 3x - 1
-7x +14 = 3x - 1
-10x = -15
x = 1,5
f) 4 (x-1) = 6 (1+x)
4x - 4 = 6 + 6x
-2x= 10
x = -5

zad.9
a) 0,2x + 0,3 = -0,5
0,2x= - 0,8
x = -4


d) - 1,5x - 3 = 0,2x + 6
- 1,7x = 9
x = - 5,3
1 5 1